CODE-SWITCHING AS LANGUAGE TEACHING STRATEGY IN EFL ONLINE CLASSROOM - Nur Amalina Zatalini (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Education practices have shifted to online classrooms in this pandemic era. The lecturers and the students met online via Zoom, g-meet, etc. This study aims to reveal the use of code-switching as a language teaching strategy in EFL online classrooms. Code-switching refers to using multiple linguistic codes to communicate by any classroom participants. This study is qualitative research. The researcher analyzes and describes the functions of code-switching the lecturers perform in their natural classroom without manipulating the variables. The data is taken through class observation and questionnaires. The class is recorded, then the utterances are transcribed. This study found that the lecturers of the undergraduate program performed situational code-switching and metaphorical code-switching. The lecturers use code-switching mostly to add some information related to the lesson. The code-switching has function as clarification, repetition, recapitulation, and socialization. The lecturers have a positive attitude in using code-switching to help students understand the lesson well.